2016
DOI: 10.1186/s40643-016-0088-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of different culture conditions for enhanced laccase production and its purification from Tricholoma giganteum AGHP

Abstract: Background:In current times, enzyme-catalyzed reactions have gained importance for the development of new chemical processes. These require the production of large quantity of enzyme at low cost. Solid-state fermentation (SSF) is an efficient process because this bioprocess has a potential to convert agro-industrial residues into valuable compounds. Hence, the current study focuses on the optimization of process parameters for the higher production of laccase using a novel basidiomycete fungi Tricholoma gigant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 38 publications
4
33
0
1
Order By: Relevance
“…Production of lignolytic gene is influenced by the initial pH of the medium. In the pH of 4 to 5 most of the white rot fungi can grow properly and also the substrate acidity decrease their growth [66]. Inoculum concentration performs a significant function in biological pre-treatment.…”
Section: Factors Influencing Biological Pre-treatmentmentioning
confidence: 99%
“…Production of lignolytic gene is influenced by the initial pH of the medium. In the pH of 4 to 5 most of the white rot fungi can grow properly and also the substrate acidity decrease their growth [66]. Inoculum concentration performs a significant function in biological pre-treatment.…”
Section: Factors Influencing Biological Pre-treatmentmentioning
confidence: 99%
“…A few studies have shown that there was production enhancement by the addition of phenolic and nonphenolic inducers. The maximum production was observed on the 12 th day with a further decline in the production after day 15 with ST02 strain (Patel and Gupte 2016). Mazumder et al (Mazumder et al, 2009) observed that Pleurotus ostreatus have strong proteolytic activity in submerged fermentation (SmF) presumably caused subsequent laccase degradation, which lowered the ultimate laccase production in SmF compared to SSF.…”
Section: Resultsmentioning
confidence: 99%
“…The different types of substrates have a notable effect on the production of laccase. The wheat straw substrate was also observed as most suitable for laccase production by T. giganteum AGHP with full colonization of substrate on the 16th day of incubation (Patel and Gupte 2016).…”
Section: Production Of Laccase Under Ssfmentioning
confidence: 96%
“…Some of the agricultural waste residues commonly used includes banana peel, apple pomace, brewery waste, wheat straw, wheat bran, rice straw, rice bran, sugarcane bagasse, etc. (Gassara et al 2011;Vivekanand et al 2011;Karp et al 2015;Patel and Gupte 2016). SSF can be applied for the synthesis of several valuable chemical intermediates with many advantages which includes enhanced fungal growth on the contact substrate in moist environment, higher biomass yields, higher product concentration, low energy requirements, less capital investment, less waste generation, simple equipment design and high product recovery (Bagewadi et al 2016a;Viniegra-González et al 2003).…”
Section: Introductionmentioning
confidence: 99%